An Analysis of Politeness and Impoliteness Strategies Used by the Main Characters in Joker Movie - Anandanaz, Tria; Rullyanti, Merry; Putra, Dhanu Ario (Amirul Bangun Bangsa Publishing, 2026)
The purpose of this study was to analyze politeness and impoliteness strategies in the movie Joker (2019) directed by Todd Phillips. This research used a descriptive qualitative method, with the Joker movie as the object and an observation checklist adapted from Brown and Levinson (1987) and Culpeper (2011) as the instrument. The researcher also identified moral values based on Driyarkara (2006) in Sukmono (2013). The results showed four politeness strategies: Bald on Record (20), Off Record (20), Positive Politeness (20), and Negative Politeness (23), with Negative Politeness being dominant. Five impoliteness strategies were found: Bald on Record Impoliteness (18), Positive Impoliteness (6), Negative Impoliteness (6), Sarcasm/Mock Politeness (9), and Withhold Politeness (2), with Bald on Record Impoliteness being dominant. The movie also delivered moral values related to empathy, kindness, fairness, acceptance, and social responsibility, as reflected in Arthur’s experiences and society’s treatment of him. These values illustrated how human behavior, both good and bad, affects individuals and society. In conclusion, Joker teaches that empathy, respect, justice, and responsibility are essential for personal and social well-being.